Mechanically reinforced biodegradable Poly(butylene adipate-co-terephthalate) with interactive nanoinclusions. (27th May 2020) - Lai, Lei; Li, Jiaxu; Liu, Pingwei; Wu, Linbo; Severtson, Steven J.; Wang, Wen-Jun
Abstract: Enhancement of mechanical properties is highly required for expanded use of biodegradable polymers like poly(butylene adipate-co-terephthalate) (PBAT). The use of nanoinclusions to develop polymer nanocomposites can provide for the desired mechanical enhancement. When using singe-type reinforcements such as silica (SiO2 ) nanoparticles or cellulose nanofibers (CNFs), however, there usually exists a reinforcing limit of the stiffness at exceedingly low volume fractions, above which the further addition of inclusions would compromise the achieved mechanical reinforcements instead. Here, we introduce an interactive nano-reinforcement approach to break such a limit for improving the mechanical properties of PBAT by combining surface-modified nanoparticles, epoxide-modified nanosilica (SiO2 -EO) and amine-treated cellulose nanofiber (CNF-NH2 ), to provide for their chemical bonding for synergistic reinforcement. Such a combination eliminates the low volume fraction limit on stiffness enhancement. Specifically, incorporation of 0.6 vol% SiO2 -EO and 0.8 vol% CNF-NH2 into PBAT increases the Young's modulus by 47% over that for PBAT, compared with a maximum increase by 16% for 0.6 vol% SiO2 -EO alone, 12% for 0.8 vol% CNF-NH2 alone, 35% for 0.8 vol% CNF-EO alone, and 37% for 0.6 vol% SiO2 -EO and 0.8 vol% CNF-EO. The tensile strength of the PBAT nanocomposite is also enhanced by chemical interaction between the modified nanoparticles with values increasing by 28% over that for nanofillers only capable of physical interactions. Storage modulus frequency sweeps indicate good compatibility between the paired nanoparticles and PBAT matrix, and electron microscopy shows good dispersion and the formation of a reinforcing network microstructure throughout the matrix film. These results provide a potential method for modifying biodegradable polymers such as PBAT for packaging and agricultural applications. Graphical abstract: An approach of using a lower dosage of two interactive surface-modified nanoparticles, epoxide-modified nanosilica and amine-treated cellulose nanofiber, to enhance mechanical properties of biodegradable poly(butylene adipate-co-terephthalate). Image 1 Highlights: Reinforcing limit of single nanoinclusion at low usages in nanocomposites was broken by using two interactive nanoinclusions.. Mechanical properties of PBAT were enhanced by introducing epoxide-modified nanosilica and amine-treated cellulose nanofiber. Good compatibility between paired nanoparticles and PBAT and excellent dispersion of nanoparticles in matrix were achieved. The study provides a potential method for modifying biodegradable polymers for packaging and agricultural applications.